2015
DOI: 10.1016/j.jphs.2015.03.006
|View full text |Cite
|
Sign up to set email alerts
|

The effect of combined treatment with canagliflozin and teneligliptin on glucose intolerance in Zucker diabetic fatty rats

Abstract: To assess the impact of concomitant inhibition of sodium-glucose cotransporter (SGLT) 2 and dipeptidyl peptidase IV (DPP4) for the treatment of type 2 diabetes mellitus (T2DM), the effect of combined treatment with canagliflozin, a novel SGLT2 inhibitor, and teneligliptin, a DPP4 inhibitor, on glucose intolerance was investigated in Zucker diabetic fatty (ZDF) rats. Canagliflozin potently inhibited human and rat SGLT2 and moderately inhibited human and rat SGLT1 activities but did not affect DPP4 activity. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 31 publications
1
13
0
Order By: Relevance
“…Finally, an effect independent of SGLT1 inhibition might have also partially influenced the results as described above. In the current study, further elevation of plasma active GLP-1 levels was observed by addition of teneligliptin, a DPP4 inhibitor, supporting the results of previous animal studies [10,11]. This finding appears to suggest a benefit of co-treatment of canagliflozin with DPP4 inhibitors for elevating circulating GLP-1 levels.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Finally, an effect independent of SGLT1 inhibition might have also partially influenced the results as described above. In the current study, further elevation of plasma active GLP-1 levels was observed by addition of teneligliptin, a DPP4 inhibitor, supporting the results of previous animal studies [10,11]. This finding appears to suggest a benefit of co-treatment of canagliflozin with DPP4 inhibitors for elevating circulating GLP-1 levels.…”
Section: Discussionsupporting
confidence: 91%
“…One patient cells located mainly in the mucosal membrane of the lower small intestine [10]. The remarkable elevation of plasma active GLP-1 levels was noted especially with co-administration of dipeptidyl peptidase 4 (DPP4) inhibitors, which block GLP-1 degradation [11]. Although a tendency toward an increase in circulating active GLP-1 by canagliflozin is reported also in healthy subjects [9], there is as yet no evidence demonstrating the effect of canagliflozin on circulating active GLP-1 in patients with type 2 diabetes.…”
Section: Originalmentioning
confidence: 99%
“…Another possible mechanism underlying the effect of the combination on postprandial glucose is that it might enhance GLP‐1 secretion. Oral administration of 100 mg of canagliflozin increased plasma total GLP‐1 after breakfast in Japanese patients with T2DM, probably because of a weak inhibitory effect of canagliflozin against SGLT1 . Although we did not measure GLP‐1 levels in the present study, the combination of teneligliptin and canagliflozin may increase active GLP‐1 levels, representing a beneficial effect of this combination.…”
Section: Discussionmentioning
confidence: 67%
“…A recent clinical study of canagliflozin found delayed intestinal glucose absorption accompanied by increased plasma GLP-1 levels in healthy subjects (Polidori et al, 2013). Furthermore, the combined treatment with canagliflozin and teneligliptin, a DPP4 inhibitor, increased plasma active GLP-1 (aGLP-1) levels in diabetic rats (Oguma et al, 2015). Because plasma GLP-1 levels were not potentiated in SGLT2-deficient mice after a meal challenge (Powell et al, 2013), it has been suggested that GLP-1 elevation by canagliflozin is mediated by a mechanism other than the inhibition of SGLT2.…”
Section: Introductionmentioning
confidence: 99%